The microflora of fermented nixtamalized corn - Sefa-Dedeh, S.; Cornelius, B.; Amoa-Awua, W.; Sakyi-Dawson, E.; Afoakwa, E.O. (International Journal of Food Microbiology, 2004)
Nixtamalization is a traditional process that improves the nutritional quality of corn. To provide a means of utilizing the nutritional benefits of nixtamalized corn and improve product acceptability, lactic acid fermentation was applied. The objective of the study was to study the microbial profile and establish the important lactobacilli of fermenting nixtamalized corn dough. Two batches of cleaned whole corn were subjected to the process of nixtamalization, using two concentrations of lime (0.5 or 1.0%), milled, made into a dough (50% moisture) and fermented spontaneously for 72 h. A control sample was prepared without alkaline treatment. pH and titratable acidity of the dough were measured. Aerobic mesophiles, lactic acid bacteria, yeasts and molds were enumerated on Plate Count Agar (PCA), deMan, Rogossa and Sharpe (MRS) Agar and Malt Extract Agar (MEA), respectively. The identity of lactobacilli present was established at the species level using API 50 CHL. The pH of all the fermenting systems decreased with fermentation time with concomitant increase in titratable acidity. Lactic acid bacteria in numbers of 1.6×109, 2.3×109 and 1.8×109 cfu/g, respectively yeasts and molds, and numbers of 8.0×107, 5.0×105 and 1.7×105 cfu/g, respectively were observed in the control and the two nixtamalized (0.5% and 1.0% lime) samples after 48 h of fermentation. Lactobacilli identified in the fermenting nixtamalized corn dough were Lactobacillus plantarum, Lactobacillus fermentum and Lactobacillus cellobiosus as well as Pediococcus spp. The study demonstrates that nixtamalized corn though alkaline in nature can be subjected to spontaneous fermentation to produce a sour product. © 2003 Elsevier B.V. All rights reserved.
Keywords: Corn; Corn dough; Fermentation; Microflora; Nixtamalization